Transdermal estrogen gel vs oral estrogen after hysteroscopy for intrauterine adhesion separation: A prospective randomized study - Yi, Tianjin; Zhang, Xiaofang; Gupta, Vani; Li, Li; Zhong, Qian (Frontiers in Endocrinology, 2023)
Background: This randomized controlled trial (RCT) aimed to compare two different routes of postoperative estrogen treatment on the improvements of menstruation, postoperative endometrial thickness, and fertility outcomes in patients with moderate to severe intrauterine adhesions (IUA). Methods: This study prospectively included 78 women (age: 25 to 45 years) with moderate to severe IUA who underwent hysteroscopic resection of adhesions between March 2019 and October 2020. The enrolled patients were randomized 1:1 into either the transdermal gel group (n = 39) or the estradiol valerate oral tablet group (n = 39) on the day of receiving hysteroscopy. Postoperative endometrial thickness, AFS (American Fertility Society) score, estrogen level, and the pattern and amount of menstruation were compared. Pregnancy information was actively collected during 1-year follow-up after the operation. Results: The postoperative endometrium thickness was improved in both groups, and both groups gained menstruation improvement rates of 67%. For patients who underwent second-look hysteroscopy (17 from the oral group and 19 from the transdermal group), the mean AFS score declined greater than 2 in both groups. For patients with postoperative pregnancy intention, the pregnancy rates at 1-year follow-up after the procedures were 40.5% and 28% in the transdermal group and oral group, respectively. Although no statistically significant difference was observed between the two groups, patients in the transdermal group had a tendency toward increased pregnancy rate. Conclusions: Transdermal administration of estrogen is equally efficacious as oral estrogen in postoperative treatment of IUA patients with a relatively safe profile. It is very likely to broaden its indication to the field of IUA. Trial Registration: This RCT was registered in the Chinese Clinical Trial Registry Center before the enrollment of the first participant. Registration No.: ChiCTR1900022110; URL: http://www.chictr.org.cn/showproj.aspx?proj=37197)